WIND ENERGY AS AN ALTERNATIVE ENERGY SOURCE(Study Case at South Coastal of Yogyakarta Special Province, Indonesia) - Baiq Liana Widiyanti (Universitas Negeri Yogyakarta, 2015)
The need of larger quantity of energy to fulfill the demand of energy, especially thefossil fuel, forced the government of almost all nation try to find the new kind of energy orknown as alternative energy resources. Fossil fuel as non-renewable energy resources wouldbe decreased by the time if the using of it not under controlled. This kind of energy resourcesused to handle almost all the people need of energy, such as for domestic uses, industrial,tourism, etc. The used of fossil fuel for that purposed mostly for generated the electricitypower (by built the power plant). Many natural energy resources can used to generateelectricity power plant, but there always be some advantages and bad impact, especially forthe environments. One of environmental friendly alternative energy resources is exploitingthe form of wind power.Keyword: alternative energy, wind energy, windmills farms, human well-being.